Remarkable Protective Effects of Nrf2-Mediated Antioxidant Enzymes and Tissue Specificity in Different Skeletal Muscles of Daurian Ground Squirrels Over the Torpor-Arousal Cycle - Wei, Yanhong; Zhang, Jie; Yan, Xia; Peng, Xin; Xu, Shenhui; Chang, Hui; Wang, Huiping; Gao, Yunfang (Frontiers in Physiology, 2019)
Hibernating mammals experience conditions of extreme oxidative stress, such as fasting, muscle disuse, and repeated hypoxic ischemia-reperfusion, during the torpor-arousal cycle. Despite this, they experience little oxidative injury and are thus an interesting model of anti-oxidative damage. Thus, in the current study, we explored the levels and underlying mechanism of oxidative stress and antioxidant capacity in three skeletal muscles [slow-twitch soleus (SOL), fast-twitch extensor digitorum longus (EDL), and mixed gastrocnemius (GAS)] of Daurian ground squirrels (Spermophilus dauricus) during hibernation. Results showed that hydrogen peroxide content in the EDL and GAS decreased significantly during pre-hibernation (PRE) and late torpor (LT) compared to levels in the summer active (SA) group. Furthermore, relative to SA levels, malondialdehyde content decreased significantly during interbout arousal (IBA) and early torpor (ET) in all three skeletal muscles and decreased in the EDL and GAS during LT. Compared with the SA group, glutathione peroxidase 1 (GPx1) and catalase (CAT) protein expression in the SOL and superoxide dismutase 1 (SOD1) and SOD2 expression in the GAS increased significantly during the entire hibernation season. Furthermore, SOD1 in the IBA group and CAT and GPx1 in the ET and LT groups increased significantly in the EDL. The activities of most tested antioxidant enzymes were higher in the IBA group than in the LT group, whereas CAT remained highly active throughout the hibernation season in all three muscles. Nrf2 and p-Nrf2 protein levels were significantly elevated in the SOL and EDL during hibernation, and increased during the PRE, IBA, and ET states in the GAS. Thus, activation of the Nrf2/Keap1 antioxidant pathway resulted in the elimination of excess reactive oxygen species (ROS). Specifically, ROS levels were maintained at physiological levels by the up-regulation of antioxidant enzyme expression in skeletal muscles under oxidative stress during hibernation, thus preventing oxidative injury over the torpor-arousal cycle. Different antioxidant patterns and oxidative stress levels were also observed among the different skeletal muscles of hibernating Daurian ground squirrels.